O valor de mercado da educaç\~ao pública - Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Publicly provided education is both an important public expenditure and a relevant in-kind transfer, often to the poorest households. This paper compares three methods to value education services and their distributive impact. The methods are: i) The first method is cost of provision, according to which education is worth what it costs the state to provide it; ii) The second method is to value educational services using the labor market as the measure of their worth; iii) The third is to match private educational expenditures, paid for by students or their parents, with equivalent public education services, and then value the latter according to the price of the former. The results from all three approaches do not fall far from each other. The imputed income from publicly provided education reduces inequality by between 3 and 4 Gini points and increases incomes by about 6%. My conclusion is that the value of public education in Brazil is close to 6% of household income and it is quite distributive, whatever the valuation method used.
Keywords: I24; D31; H44; I38; 330; educational service valuation; inequality; education; welfare; returns to education; hedonic pricing